2002
DOI: 10.1007/s00125-002-0953-z
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β induced protein changes in diabetes prone BB rat islets of Langerhans identified by proteome analysis

Abstract: Aims/hypothesis. Type I (insulin-dependent) diabetes mellitus is characterized by selective destruction of the insulin producing beta cells. Interleukin-1β (IL-1β) modulates the beta-cell function, protein synthesis, energy production and causes apoptosis. We have previously shown changes in the expression of 82 out of 1 815 protein spots detected by two dimensional gel electrophoresis in IL-1β exposed diabetes prone Bio Breeding (BB-DP) rat islets of Langerhans in vitro. The aim of this study was to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Secretagogin has previously been suggested to be involved in beta cell homeostasis by protecting against IL-1β-mediated beta cell destruction in diabetes-prone biobreeding rat islets [ 43 ]. These results are in contrast with our study, which indicated that cytokines did not change the apoptotic susceptibility of secretagogin silenced human beta cells.…”
Section: Discussionmentioning
confidence: 99%
“…Secretagogin has previously been suggested to be involved in beta cell homeostasis by protecting against IL-1β-mediated beta cell destruction in diabetes-prone biobreeding rat islets [ 43 ]. These results are in contrast with our study, which indicated that cytokines did not change the apoptotic susceptibility of secretagogin silenced human beta cells.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic technique has been widely used to investigate the protein changes elicited by exposure of islets or insulinoma cells to glucose [21], [22], cytokines [23], [24] and others substances [25], [26]. Here we report the proteomic characterization of β-TC3R.…”
Section: Resultsmentioning
confidence: 96%